Session RPE and salivary immune-endocrine responses to simulated and official basketball matches in elite young male athletes - Moreira, A.; Crewther, B.; Freitas, C. G.; Arruda, A. F. S.; Costa, E. C.; Aoki, M. S. (The Journal of Sports Medicine and Physical Fitness, 2012)
The present study compared the ratings of perceived exertion (RPE) and immune-endocrine (IgA and cortisol) responses to simulated training matches (TM) and official matches (OM) in elite young male basketball players (N.=10). Saliva samples were collected from each player before and after three TM and two OM and subsequently tested for cortisol and IgA concentrations by immunoassay. The perceived intensity of each match was rated using a RPE scale (CR-10). The training match and official match data were pooled to provide an aggregate value for each setting. The session RPE scores from the OM were significantly (P<0.05) greater than the simulated TM. Pre- and postcortisol concentrations assessed during the OM were also found to be significantly higher than the TM (P<0.05). No significant changes in salivary IgA concentrations were observed across either the simulated or official match settings. In summary, the OM induced greater RPE and salivary cortisol responses than the simulated TM, probably due to the additional stressors associated with real competition. The data also suggests that acute changes in cortisol concentrations do not play a role in the regulation of salivary IgA under the current testing conditions.